Charge Transfer Mechanism in Type II WO3/Cu2O Heterostructure - Anna A. Murashkina; Aida V. Rudakova; Tair V. Bakiev; Alexei V. Emeline; Detlef W. Bahnemann (Nanomaterials)
In this study, we explore the charge transfer mechanism between WO3 and Cu2O in heterostructured WO3/Cu2O electrodes and in a WO3||Cu2O tandem photoelectrochemical cell. The physical–chemical characterizations of the individual WO3 and Cu2O electrodes and the heterostructured WO3/Cu2O electrode by XRD, XPS, and SEM methods confirm the successful formation of the target systems. The results of photoelectrochemical studies infer that in both the heterostructured WO3/Cu2O electrode and WO3||Cu2O tandem photoelectrochemical cell, the major mechanism of charge transfer between WO3 and Cu2O is a realization of the Z-scheme.